‘Refugees’ nightmares’: Motives of escape and anxiety in Gertrud Leutenegger’s novel "Späte Gäste" (2020) - Górska, Ewa; Sośnicka, Dorota (Transfer. Reception Studies, 2023)
Gertrud Leutenegger’s latest novel Späte Gäste [The Late Guests] (2020) revolves around the theme of love and death – like many of her earlier books. At the same time, however, various motives of escaping and saving life or starting a new life, as well as the fear and anxieties associated with them, come to the fore. This novel with an autobiographical tinge is, on the one hand, a kind of farewell to a deceased loved one, – whose aggression, however, the nameless first-person narrator had to escape from, and on the other hand, it draws special attention to the highly relevant issue of the current refugee waves. Against the background of a brief description of the unique narrative style of the Swiss writer, honored with many literary awards, the article focuses on the dominant themes of escape and anxiety in the analyzed work, interpreting the novel on the one hand as a kind of ‘farewell book’, yet on the other hand also as a ‘welcome book’, which shows how necessary it is to give refugees – paraphrased in the novel’s title as “late guests” – a chance for a new beginning. An important role here is played by the warning from the myth of Orpheus not to look back, which the novel refers to many times. This warning is also in the focus of interpretation pertinent to both the traumatic experiences of the first-person narrator and the shocking ordeals of refugees and emigrants, who often appear in the analyzed work.